On the troubling use of plastic 'habitat' structures for fish in freshwater ecosystems - or - when restoration is just littering - S.J. Cooke; M.L. Piczak; J.C. Vermaire; A.E. Kirkwood (Canadian Science Publishing, 2023)
The creation and deployment of plastic structures made out of pipes and panels in freshwater ecosystems to enhance fish habitat or restore freshwater systems have become popularized in some regions. Here, we outline concerns with these activities, examine the associated evidence base for using plastic materials for restoration, and provide some suggestions for a path forward. The evidence base supporting the use of plastic structures in freshwater systems is limited in terms of ecological benefit and assurances that the use of plastics does not contribute to pollution via plastic degradation or leaching. Rarely was a cradle-to-grave approach (i.e. the full life cycle of restoration as well as the full suite of environmental consequences arising from plastic creation to disposal) considered nor were decommissioning plans required for deployment of plastic habitats. We suggest that there is a need to embrace natural materials when engaging in habitat restoration and provide more opportunities for relevant actors to have a voice regarding the types of materials used. It is clear that restoration of freshwater ecosystems is critically important, but those efforts need to be guided by science and not result in potential long-term harm. We conclude that based on the current evidence base, the use of plastic for habitat enhancement or restoration in freshwater systems is nothing short of littering.